Observed and simulated variability of extreme temperature events over South America - Rusticucci, Matilde Monica (2012)
This invited review paper tends to summarise the results based on the variability of occurrence of temperature extremes in South America. The first thing to note is that there is a geographical imbalance with respect to the number of published studies on temperature extremes. Most of the results come from the southern part of South America, east of the Andes, and a few from the northern part of the continent and for the Altiplano. The workshop organised by the ETCCDMI in Brazil was the first time to have the opportunity to collect information in a regional way and present trends in extreme daily temperatures. A better geographical picture enhanced with more data show significant geographical trends in warm (positive) and cold (negative) nights over Southern South America and over the northern South America coast. All other studies based on smaller regions also agree in finding the most significant trends in the evolution of the minimum temperature, with positive trends in almost all studies on the occurrence of warm nights (or hot extremes of minimum temperature) and negative trend in the cold extremes of the minimum. On the other hand, there is little agreement on the variability of maximum temperature. Generally the maximum temperature in southern South America has decreased, in opposition to the case of northern South America where it has increased. Strong decadal and interannual variability have been found in the occurrence of cold extremes. Reanalysis and climate models underestimate the intensity of extremes, mainly near the Andes. The studies trying to understand the dynamics of the circulation that leads to the occurrence of these extremes are analysed from its occurrence in almost all scales from the synoptic, intraseasonal, seasonal, annual, and multi-year linear trend with different methodologies, also, indentifying the local and remote forcing. A gap was found in studies that relate some specific local forcing (like changes in land use) and compare it with the remote ones. Different aspects of the occurrence of the temperature extremes are still missing in some regions of the continent.